2023
DOI: 10.21511/imfi.20(2).2023.18
|View full text |Cite
|
Sign up to set email alerts
|

Board characteristics and firm value: The moderating role of capital adequacy

Abstract: The global financial crisis increased corporate world uncertainties. Therefore, to meet these challenges, firms take a more proactive approach to tackling various corporate governance and firm value initiatives and policies. This study aims to explore the moderating effect of capital adequacy on the relationship between board characteristics and the firm value of listed banks in Pakistan. To obtain a more robust empirical model and results, this study incorporates moderator and control variables. This study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Various scientists have researched gender differences in business management or decision-making. Jagirani et al (2023) stressed the need to balance women and men on the board of directors. Hapsoro et al (2022) showed that only the presence of several women on the board of directors has a positive relationship with firm value.…”
Section: Verification Of Hypothesesmentioning
confidence: 99%
“…Various scientists have researched gender differences in business management or decision-making. Jagirani et al (2023) stressed the need to balance women and men on the board of directors. Hapsoro et al (2022) showed that only the presence of several women on the board of directors has a positive relationship with firm value.…”
Section: Verification Of Hypothesesmentioning
confidence: 99%